KEKUATAN HUKUM HASIL TES DEOXYRIBONUCLEIC ACID (DNA) TERHADAP STATUS ANAK DILUAR NIKAH YANG TIDAK DIAKUI OLEH AYAH BIOLOGISNYA DALAM PERSPEKTIF HUKUM PERDATA - Maria Goreti Beto Tapobali (Fakultas Hukum Universitas Janabadra, 2021)
Marriage is an important event that occurs in human life and is considered a sacred event and therefore relies heavily on religious elements in its continuity. Religiosity in marriage is reflected in Law Number 1 of 1974 concerning Marriage. According to Article 57 of Law Number 1 of 1974 concerning Marriage (Marriage Law), what is meant by mixed marriage in this law is marriage between two people who in Indonesia are subject to different laws, due to differences in citizenship and one of the parties is an Indonesian citizen. However, in the event that the mixed marriage which is held abroad can be declared valid according to Indonesian law, within 1 (one) year after the husband and wife return to the territory of Indonesia, their marriage certificate must be registered at the Civil Registry Office where they live. as in the provisions of Article 56 paragraph 2 of the Marriage Law. This paper mainly discuss about the complexity and cause of mixed marriage in Indonesia